Avaliação da corrosão do aço carbono ASTM A-36 quando em contato com biodiesel de variadas matrizes e diesel aditivado com 5% de biodiesel - Milene Adriane Luciano (2011)
The main objective of this study is to assess the corrosive potential of samples of vegetable oil from soybeans, macaúba and jatropha, their biodieseis (B100), blends of diesel with 5% of biodiesel (B5) and diesel when pure in contact with carbon steel blades ASTM A-36 used in the manufacture of fuel tanks. The accelerated aging test samples of fuel in contact with the steel consisted of the partial immersion of slides ineach sample fuel in a single autoclave at 100°C and oxygen pressure of about 720kPa. The samples were examined by weight loss, scanning electron microscopy (SEM) and perfilometry. The parameters of acid value, peroxide value, water value, density and viscosity of the fuel samples were evaluated before and after the accelerated agingtests. Also we have used elemental analysis and thermogravimetry to evaluate the fuel samples after the tests. The results indicate that the corrosion process of carbon steel ASTM A-36 is selective and thermodynamically favorable in touch with all the fuel samples, but the reaction speed is very slow resulting in a change in roughness of 0.5micrometers. The presence of biodiesel in diesel fuel has increased its potential corrosive, especially when using the matrix macaúba. The addition of antioxidants on biodiesel from soybeans and soybean oil was effective in slowing the rate of oxidation reactions, making them less aggressive.